NUMERICAL INVESTIGATION OF BLOOD FLOW FEATURES IN INTRACRANIAL SACCULAR ANEURYSMS - Mercan, H.; Atalik, K. (YILDIZ TECHNICAL UNIV, 2018)
This study aims to provide insight about how the hemodynamic factors change with artery curvature for a developing aneurysm during a cardiac cycle. The aneurysm is investigated in terms of the vortical structure and the shear stress along the curved artery wall for three developing stages (initial, intermediate and terminal stages), for three instances of a cardiac cycle (diastole end, systole peak and diastole start) and for three different vascular geometries. The stream function vorticity formulation is used with Newtonian constitutive relation. During the systole peak instance for all aneurysm stages, the central vortex squeezes the streamlines towards the distal neck of the aneurysm leading to maximum wall shear stress in the vicinity of the distal wall of the aneurysm. The radius of curvature of the artery and inertial forces increased the wall shear stress along the aneurysm wall. The wall shear stress changes direction and concentrates in the vicinity of the distal neck for all artery geometries. Secondary vortices are observed in the terminal stage during diastole end and diastole start instances for the straight arteries and lead to shear stress fluctuations along the wall. The observations of this study are discussed together with the relevant clinical and numerical literature.
Keywords: Hemodynamics; Intracranial Aneurysm; Pulsatile Flow; Stream Function-Vorticity Formulation; Computational Fluid Dynamics; Wall Shear Stress Analysis; CEREBRAL ANEURYSM; AORTIC-ANEURYSMS; DYNAMICS; MODELS; ARTERY; Thermodynamics